Pelatihan Metode Pembelajaran Contextual Teaching Learning untuk Meningkatkan Motivasi Belajar Siswa - I Made Sonny Gunawan; Sarilah Sarilah; I Made Gunawan; Kholisussadi Kholisussadi (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of carrying out this community service activity is to increase the knowledge and understanding of kindergarten teachers about the application of Contextual Teaching Learning learning methods in increasing student learning motivation. The method used in this service is to provide counseling in the form of training for kindergarten teachers and provide assistance for six months. The participants in this community service activity were 6 teachers at Darul Muhsinin Kindergarten, Enjak Hamlet, Labulia Village, West Lombok Regency. The results of this community service indicate an increase in the skills of kindergarten teachers in designing and implementing effective learning methods for students that can increase student learning motivation.